THE EFFECTIVENESS OF GAME BASED LEARNING METHOD WITH PERFECT NUMBER MEDIA ON CREATIVE THINKING ABILITY OF ELEMENTARY SCHOOL STUDENTS - Purwanti, Kartika Yuni; Putra, Lisa Virdinarti (Universitas Nusantara PGRI Kediri, 2022)
This study aims to determine the effectiveness of Game Based Learning Method with Perfect Number Media on Creative Thinking Ability of Elementary School Students. The use of perfect number media aims to make learning more interesting and improve students' creative thinking skills. This study uses a quantitative approach to the type of experimental research. This research was conducted at SDN Jubelan 01, Sumowono District, Semarang Regency, Central Java. The population in this study were all students at SDN Jubelan 01. The research sample was grade IV students at SDN Jubelan 01. The results showed that the game-based learning method assisted by perfect number media was effective in improving students' creative thinking skills. The results of the t test show that there is a difference in the average learning value of the experimental class which is higher than the average value of the control class learning and the significance level is < 0.05, then is accepted. The results of the regression test showed that there was an effect as evidenced by the significance value of students' creative thinking ability of 0.038 where this value was less than 0.05, then the hypothesis was accepted. The results of the paired sample t-test showed a significance level of <0.05, namely 0.00 <0.05, then was accepted. The data on the value of creative thinking ability also shows that the percentage of the experimental class is greater than the control class.